Selective Aggregation of Fine Spodumene from Quartz with Anionic Polyacrylamide Flocculant and Calcium Activator - Danni Luo; Wei Sung Ng; George V. Franks (Colloids and Interfaces)
Fine spodumene particles are challenging to treat by froth flotation and are often discarded. An approach to recover the lithium-bearing mineral is to selectively aggregate fine spodumene into larger sizes that are amenable to recovery by flotation. This research investigated the aggregation behaviour of spodumene and the gangue minerals K-feldspar and quartz, using commercially available anionic polyacrylamide flocculants. Calcium ions were used as activators that facilitated the selective adsorption of the carboxylate groups in the anionic flocculants onto the spodumene surface. The calcium ions decreased the magnitude of the negative zeta potential and reversed the zeta potential to positive for spodumene and K-feldspar, but not for quartz, below pH 10. Calcium concentrations of 312.5 g/t enhanced the adsorption of anionic polymers onto spodumene and K-feldspar, inducing aggregation, while quartz was aggregated only above 5000 g/t. Increasing the polymer concentration increased the aggregate size for spodumene and K-feldspar, but had little effect on quartz. In situ sizing and turbidity measurements indicated the optimal conditions for spodumene aggregation were 625 g/t of calcium and 63–84 g/t of the 58% anionic-charged polyacrylamide at pH 8.5. The sedimentation results showed limited separation due to quartz entrapment in the aggregates. Anionic polyacrylamide flocculants with calcium activators can aggregate fine spodumene particles.